Responses in the Inferior Colliculus of the Guinea Pig to Concurrent Harmonic Series and the Effect of Inactivation of Descending Controls - Nakamoto, Kyle T. (American Physiological Society, 2010)
One of the fundamental questions of auditory research is how sounds are segregated because, in natural environments, multiple sounds tend to occur at the same time. Concurrent sounds, such as two talkers, physically add together and arrive at the ear as a single input sound wave. The auditory system easily segregates this input into a coherent percept of each of the multiple sources. A common feature of speech and communication calls is their harmonic structure and in this report we used two harmonic complexes to study the role of the corticofugal pathway in the processing of concurrent sounds. We demonstrate that, in the inferior colliculus (IC) of the anesthetized guinea pig, deactivation of the auditory cortex altered the temporal and/or the spike response to the concurrent, monaural harmonic complexes. More specifically, deactivating the auditory cortex altered the representation of the relative level of the complexes. This suggests that the auditory cortex modulates the representation of the level of two harmonic complexes in the IC. Since sound level is a cue used in the segregation of auditory input, the corticofugal pathway may play a role in this segregation.